LATE QUATERNARY LANDSCAPE EVOLUTION OF THE UPPER DNISTER VALLEY, WESTERN UKRAINE - Huhmann M.; Brückner H.; Kremenetski K.V.; Hiller A. (My University, 2004)
The broad and flat valley of the upper Dnister in western Ukraine is characterized by a complex setting of ecotopes and a relatively natural state of floodplain dynamics. Excellent geo-archives–extended peat bogs and postglacial river terraces–document late Quaternary landscape evolution with special regard to changes in fluvial morphodynamics, vegetation and human impact. The terraces were studied by detailed geomorphological mapping as well as sedimentological and pedological analyses in connection with information from historical maps. Vegetation history was studied by palynological methods in combination with radiocarbon dating.Two Late Pleistocene (NT1 and NT2) and seven Holocene (H1–H7) river terraces are evident. The ecological transformation during the period of climatic warming at the end of the last glacial maximum (LGM) caused the most significant change in runoff and sediment load, as well as in the vegetation cover. The Dnister changed from a braided to a meandering river system. It was soon after the spreading of postglacial forests with an increasing dominance of broadleaved trees that the pollen diagrams reflected the first signs of anthropogene influence. Intensified agricultural land use since the Iron Age is mirrored in the increasing amount of herbaceous pollen as well as the rise of fluvial sediment redeposition. Modern hydraulic engineering on the Dnister has caused visible transformations. Because of these impacts, the stability of the upper Dnister ecosystem has decreased significantly and is now highly sensitive to environmental change.
Keywords: Floodplain evolution; Holocene; Radiocarbon dating; Palynology; Vegetation history; Ukraine; Dnister; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен